COLLUSION IN MARKETS CHARACTERIZED BY ONE LARGE BUYER: LESSONS LEARNED FROM AN ANTITRUST CASE IN RUSSIA - Andrey E. Shastitko; Svetlana V. Golovanova (National Research University Higher School of Economics, 2014)
This paper demonstrates that even established and verified facts of agreements among producers are not a sufficient condition for cartel identification and, as a consequence, prosecution of agreement participants. Such requires looking at institutional details and the wider context of these and similar appearances or occurrences of documents and actions when qualifying the actions of market participants and their effects. This paper discusses a recent antitrust case brought against Russian manufacturers of large diameter pipes (LDPs) that examined supposedly abusive practices by these firms that were contrary to the law on the Protection of Competition, which prohibits market division. The case under consideration illustrates the importance of investigating institutional details when qualifying the actions of market participants and their effects. An analysis of the materials in this case using modern economic theory indicates that the presence of collusion is inconsistent with the active participation of the main consumer of LDPs in that agreement. The chosen format for the cooperation between pipe manufacturing companies and OJSC Gazprom, namely indicative planning, may be explained from the perspective of reducing contract risk in an environment characterized by large-scale private investments. – – , , , . . , (), , , . . , . , , , .
Keywords: K21; B52; 330; collusion; antitrust policy; credible commitments; indicative planning; contract risk